The Studies on Embryo Production from Hanwoo Cows with High Offspring Meat Quality Grade and Embryo Transfer - Hae-Lee Lee; Jae-Hee Park; Yong-Su Kim; Jong-Gug Kim (The Korean Society of Animal Reproduction and Biotechnology, 2019)
These studies were conducted to evaluate developmental competence of follicular oocyte collected from the ovaries of Hanwoo cows with the high offspring meat quality (1++ and 1+ grade). Cumulus oocyte complexes from individual cows were matured, fertilized and cultured using protocols of in-vitro maturation (IVM), in-vitro fertilization (IVF) and in-vitro culture (IVC). The rates of blastocyst development from Hanwoo cows with the offspring meat quality grades of 1++ and 1+ were 18.6 and 21.2%, respectively. The rates of blastocyst development were 26.3, 20.7, 20.7, 17.2 and 31.2% from Hanwoo cows with the meat quality grades of 1++, 1+, 1, 2 and 3, respectively. Fiftyseven transferable embryos were recovered from 11 Hanwoo donor cows (5.2/head) with the high offspring meat quality grades of 1++ and 1+ in vivo, and the pregnancy rate after embryo transfer was 61.1%. In conclusion, these results suggest that in vitro embryo production from the ovaries of cows with the high meat quality grades using individual culture system can be used an efficient method for livestock improvement. In addition, for the successful industrialization of embryo transfer, conception rate should be improved.